1977
DOI: 10.3758/bf03209233
|View full text |Cite|
|
Sign up to set email alerts
|

Acquisition of barpressing in rats following experience with response-independent food

Abstract: In a three-group experiment, one group of rats (response-contingent) learned to contact a food cup for Noyes food pellets delivered according to a fixed-ratio schedule of reinforcement. Subjects in another group received a response-independent pellet each time its yoked counterpart earned one. A third (control) group received the same amount of food as the other two groups each day, but the pellets were delivered in mass. Following this training, the rats were placed in a novel experimental chamber in which al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
2
4

Year Published

1980
1980
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
0
14
2
4
Order By: Relevance
“…Neither the 30-day group nor the "live-in" group differed from the I-day group. Wheatley , Welker, and Miles (1977) had reported that deficits in instrumental responding for food were observed in rats given prior experience with noncontingent food. However, they subsequently reported (Wheatley, Welker, & Miles, 1978) that there had been errors in the statistical analysis and that the differences between the noncontingent and control groups actually were not significant.…”
mentioning
confidence: 99%
“…Neither the 30-day group nor the "live-in" group differed from the I-day group. Wheatley , Welker, and Miles (1977) had reported that deficits in instrumental responding for food were observed in rats given prior experience with noncontingent food. However, they subsequently reported (Wheatley, Welker, & Miles, 1978) that there had been errors in the statistical analysis and that the differences between the noncontingent and control groups actually were not significant.…”
mentioning
confidence: 99%
“…160;Maier& Seligman, 1976)-since response speed remained unaffected. However, thispossibility does not account for the failure to observethe effect in a barpress test (Wheatley et al, 1977) or the observation of a facilitation effect. Therefore, the present series of experiments attempted to establish the conditions under which the interference effect could be observed reliably in the appetitive situation.…”
mentioning
confidence: 99%
“…Experiments in which rats have been exposed to uncontrollable appetitive reinforcers have also produced divergent effects, ranging from the interference effect Copyright 1988 Psychonomic Society, Inc. JOB (Oakes, Rosenblum, & Fox, 1982) to failure to observe an effect (Wheatley, Welker, & Miles, 1977, erratum 1978 to facilitation (Beatty & Maki, 1979;Calef et al, 1984). Methodological considerations also render some resultsambiguous.…”
mentioning
confidence: 99%
“…Capelari e Hunziker (2005) utilizaram um procedimento análogo ao tradicionalmente utilizado no estudo do desamparo com ratos, mas substituíram os estímulos aversivos incontroláveis por estímulos apetitivos incontroláveis. Seus resultados mostraram que a história com estímulos apetitivos incontroláveis não afetou a aprendizagem posterior do comportamento de fuga, achados corroborados por alguns estudos (Beatty & Maki, 1979;Calef et al,1984), mas não por outros (Caspy & Lubow, 1981;Enberg, Welker, Hansen & Thomas, 1972;Ferrándiz & Vicente, 1997;Job, 1987;Sonoda & Hirai, 1992;Welker, 1976;Wheatley, Welker & Miles, 1977). Do mesmo modo como a incontrolabilidade não se encontra suficientemente isolada da natureza do estímulo incontrolável, o papel do uso de choques elétricos no desamparo aprendido também carece de especificação.…”
Section: Uniterms: Verbal Behavior Learned Helplessness Behavioral unclassified